Perinatal Testicular Torsions: 21 Years Clinical Experience - Tartar, T.; Sarac, M.; Bakal, U.; Genc, E.; Onur, Mr; Kazez, A. (Medcom Limited, 2023)
Purpose: Perinatal testicular torsion (PTT) diagnosis and treatment management are difficult due to its rare occurrence and uncertain aetiology. Methods: The demographic data, complaints at admission, radiologic characteristics, diagnosis and treatment methods of patients who underwent follow-up and treatment for PTT were recorded. Findings: Of the patients, 50% had PTT on the right testicle, 30% had PTT on left testicle, and 20% had bilateral PTT. All patients except for one had discolouration in the scrotum. During the examinations of the patients, twisted testicles were palpated as being harder than normal. In 70% of the cases, blood flow could not be visualised in colour doppler ultrasonography (CDUS). Hydrocele was present on the opposite side of the affected testicle in 60% of the cases. Orchiectomy+fixation on the opposite testicle were performed on 10 of the 12 twisted testicles. Conclusions: Physical examination and CDUS are the primary methods used for diagnosis of PTT. The presence of hydrocele in the opposite scrotum can be a warning with regards to PTT. Due to the potential of contralateral torsion, fixation must be performed on the opposite testicle during the same session/ intervention. © 2023, Medcom Limited. All rights reserved.
Keywords: Fixation; Intrauterine; Newborn; Prenatal; Testicular torsion